Coherent J/[psi] photoproduction at forward rapidity in ultra-peripheral Pb-Pb collisions at √sNN=5.02 TeV - Acharya, Shreyasi; Angelov, Venelin; Arslandok, Mesut; Danisch, Meike; Feuillard, Victor; Glässel, Peter; Kim, Jiyoung; Kim, Minjung; Köhler, Markus Konrad; Pachmayer, Yvonne C.; Reygers, Klaus; Schicker, Rainer; et al. (Physics letters, 2019)
The ALICE collaboration performed the first rapidity-differential measurement of coherent J/ψ photoproduction in ultra-peripheral Pb-Pb collisions at a center-of-mass energy sNN=5.02 TeV. The J/ψ is detected via its dimuon decay in the forward rapidity region (−4.0<y<−2.5) for events where the hadronic activity is required to be minimal. The analysis is based on an event sample corresponding to an integrated luminosity of about 750 μb−1. The cross section for coherent J/ψ production is presented in six rapidity bins. The results are compared with theoretical models for coherent J/ψ photoproduction. These comparisons indicate that gluon shadowing effects play a role in the photoproduction process. The ratio of ψ′ to J/ψ coherent photoproduction cross sections was measured and found to be consistent with that measured for photoproduction off protons.
ALICE Collaboration*: Shreyasi Acharya, Venelin Anguelov, Mesut Arslandok, Meike Danisch, Victor Feuillard, Peter Glässel, Jiyoung Kim, Minjung Kim, Markus Konrad Köhler, Yvonne C. Pachmayer, Klaus Reygers, Rainer Schicker, Alexander Schmah, Marten Ole Schmidt, Johanna Stachel, Bernd Windelband [und 1011 weitere]
Im Titel ist "Psi" als griechischer Buchstabe dargestellt
Im Titel steht der Ausdruck "sNN" unter dem Wurzelsymbol, "NN" ist dabei tiefgestellt
Gesehen am 20.05.2020